Improving Antibody‐Tubulysin Conjugates through Linker Chemistry and Site‐Specific Conjugation. (12th February 2021) - Hamilton, Joseph Z.; Pires, Thomas A.; Mitchell, Jamie A.; Cochran, Julia H.; Emmerton, Kim K.; Zaval, Margo; Stone, Ivan J.; Anderson, Martha E.; Jin, Steven; Waight, Andrew B.; Lyon, Robert P.; Senter, Peter D.; et al.
Abstract: Tubulysins have emerged in recent years as a compelling drug class for delivery to tumor cells via antibodies. The ability of this drug class to exert bystander activity while retaining potency against multidrug‐resistant cell lines differentiates them from other microtubule‐disrupting agents. Tubulysin M, a synthetic analogue, has proven to be active and well tolerated as an antibody‐drug conjugate (ADC) payload, but has the liability of being susceptible to acetate hydrolysis at the C11 position, leading to attenuated potency. In this work, we examine the ability of the drug‐linker and conjugation site to preserve acetate stability. Our findings show that, in contrast to a more conventional protease‐cleavable dipeptide linker, the β‐glucuronidase‐cleavable glucuronide linker protects against acetate hydrolysis and improves ADC activity in vivo . In addition, site‐specific conjugation can positively impact both acetate stability and in vivo activity. Together, these findings provide the basis for a highly optimized delivery strategy for tubulysin M. Abstract : Stability and activity : Antibody‐tubulysin conjugates were evaluated for activity and acetate stability as a function of linker chemistry and conjugation site. Results show the glucuronide linker and S239 engineered cysteine conjugation preserve the acetate in circulation and improve in vivo activity relative to a dipeptide linker and endogenous cysteine conjugation.